An Analysis on the Production of Livestock and its impact on Food Security - Espino, Marlou Evan; Gacelos, Aeron Jacob; Cabauatan, Ronaldo (International Journal of Social and Management Studies, 2022)
Food security refers to both physical and financial access to food. Meat, like the economy, has supply and demand, with excessive demand driving up prices and a reduction in food supply driving up prices as well. This research focuses on the topic of rising hunger and malnutrition, which can be due to a lack of food security. Low food security refers to a lack of safe and nutritious food, which can be affected by a variety of factors mainly on the supply and production side of Livestock. This research project also intends to (1) assess the production trend, and then include substantial evidence that will aid in preventing meat overproduction/underproduction and ensuring its sustainability and sufficiency for future generations. (2) determine whether current livestock production satisfies current livestock demand using production data. (3) determine the country’s food security for the past 30 years and the reasons to achieve it.